OPTIMASI KOMPOR BIOMASSA TIPE UP DRAFT PENGHASIL LISTRIK BERBASIS TERMOELEKTRIK - Septian Bayu Rizky Pratama (2020)
Biomass stove is a technology with fuel in the form of vegetable waste to ignite the fire of the stove and the waste heat from the biomass stove can be reused as an electricity generator, which is then converted through thermoelectric. The purpose of this paper is to develop a design that fits the DFMA method so as to simplify the assembly process and shorten the total assembly time and to produce a thermoelectric-based up draft type biomass stove that can reduce agricultural, livestock, plantation or other vegetable waste, which can holds 1,5 kg of biomass fuel and can also generate electricity by utilizing the heat from the stove. From the results of the study resulted in a design of the application of DFMA, where there are some changes that refer to the method used, namely simplifying the form of components, then also the process of merging, and eliminating the minimal functioning components in the machine structure with the aim of reducing production time and total production costs. The design of the development has a body dimensions of 50cm x 94cm x 30cm and an inner furnace of 40cm x 78,5cm x 25cm. The design results from the application of DFMA have better and optimal efficiency after development.